The Impact of Deviant Behavior on Juvenile Delinquency: Current State of the Problem - Mikhail Fedorovich Kostyuk; Elena Vladimirovna Kunts (Universidad Hemisferios, 2022)
The relevance of this research stems from the fact that in the modern world, the problem of juvenile delinquency is especially acute. Economic inequality, mass globalization, free access to the means of communication, the development of democracy, as well as various social phenomena often cause negative reactions among adolescents. The research goal was to give a comprehensive scientific substantiation of the problem of juvenile delinquency, to consider the impact of deviant behavior on its emergence, to identify its causes and preventive measures, and to develop proposals for their improvement. The methodological basis of the research included a set of techniques and methods for studying this phenomenon of social life. The study revealed that juvenile delinquency remains a serious problem. The negative trend related to the worsening economic situation and lowering living standard in Russia, including minors, results in the higher psychological and emotional overload and the deepening crisis in family relations, which leads to the reemergence of such social phenomenon as child neglect. The scientific novelty of the study lies in the fact that this paper assesses the criminological features of the current state of juvenile delinquency. The theoretical significance of the research includes the deeper scientific analysis of the problem, which provides a scientific basis for its further development. The practical significance implies that the theoretical conclusions obtained in this study can be used for further study of juvenile delinquency and developing measures for its prevention.